Closing the yield gap of soybean (Glycine max (L.) Merril) in Southern Africa: a case of Malawi, Zambia, and Mozambique - Omondi, John Okoth; Mkuhlani, Siyabusa; Mugo, Jane; Chibeba, Amaral Machaculeha; Chiduwa, Mazvita Sheila; Chigeza, Godfree; Kyei-Boahen, Stephen; Masikati, Patricia; Nyagumbo, Isaiah (Frontiers in Agronomy, 2023)
Smallholder farmers in Sub-Saharan Africa (SSA) are increasingly producing soybean for food, feed, cash and soil fertility improvement. Yet, the difference between the smallholder farmers’ yield and either the attainable in research fields or the potential from crop models is wide. Reasons for the yield gap include low to non-application of appropriate fertilizers and inoculants, late planting, low plant populations, recycling seeds, etcetera. Here, we reviewed literature on yield gap and the technologies for narrowing it, modelled yields through the right sowing dates and suitable high-yielding varieties in APSIM. Results highlighted that between 2010 and 2020 in SSA , soybean production increased; however, it was through an expansion in the cropped area rather than yield increase per hectare. Also, the actual smallholder farmers’ yield was 3.8, 2.2, and 2.3 times lower than the attainable yield in Malawi, Zambia and Mozambique, respectively. Through inoculants, soybean’s yield increased by 23.8%.Coupling this with either 40 kg ha-1 of P or 60 kg ha-1 of K boosted the yields by 89.1% and 26.0%, respectively. Overall, application of 21–30 kg ha-1 of P to soybean in SSA, could increase yields by about 48.2 %. Furthermore, sowing at the right time increased soybean yield by 300%.. Although these technologies enhance soybean yields, they are not fully embraced by smallholder farmers. Hence, refining and bundling them in a digital advisory tool will enhance availability of the correct information to smallholder farmers at the right time and improve soybean yields per unit area.